Different methods for (3+1)-dimensional space-time fractional modified KdV-Zakharov-Kuznetsov equation - Guner, Ozkan; Aksoy, Esin; Bekir, Ahmet; Cevikel, Adem C. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this paper, the fractional derivatives in the sense of modified Riemann-Liouville derivative and the exp-function method, the (G'/G)-expansion method and the generalized Kudryashov method are used to construct exact solutions for (3 + 1)-dimensional space-time fractional modified KdV-Zakharov-Kuznetsov equation. This fractional equation can be turned into another nonlinear ordinary differential equation by fractional complex transformation and then these three methods are applied to solve it. As a result, some new exact solutions are obtained. The three methods demonstrate power, reliability and efficiency. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Exp-function method; (G '/G)-expansion method; Generalized Kudryashov method; Modified Riemann-Liouville derivative; Space-time fractional modified; KdV-Zakharov-Kuznetsov equation; NONLINEAR EVOLUTION-EQUATIONS; TRAVELING-WAVE SOLUTIONS; 1ST INTEGRAL METHOD; (G'/G)-EXPANSION METHOD; Mathematics